Takluknya Kota Makkah dan Islamnya Abu Sofyan (Sebuah Catatan Historis Komunikasi Dakwah Muhammad SAW Melalui Pendekatan Psikologis) - Drs. Amrullah Zaini, M.I.Kom (UIN Antasari Banjarmasin, 2015)
Objectives communication da'wah Muhammad within a period of 23 years is the entire of society of Mecca and Medina, Until to around the country, so that the communication activities da'wah Muhammad called the period of Mecca and Medina to the situation communicant da'wah varied, heterogeneous and complete with the complexity of the various aspects, particularly in terms of intellectual capacity and psychological condition of the prophet that is certainly different from the background of each individual group as a communicant of da'wah messages. A strategic step that built the prophet Muhammad is the agreement with the Treaty of Hudaybiyyah Mecca although written in favor of the Quraysh, but politically and psychologically precisely the Islamic da'wah victory with concrete evidence was subject to lap Mecca Muhammad.